THE IMPORTANCE OF DRY PORT IN THE ORGANISATION OF URBAN SPACE AND THE OPTIMISATION OF PORT ACTIVITY: A CASE STUDY OF THE CITY OF SKIKDA - Amiour Amel; Boulehouche Allaoua (International Journal of Innovative Technologies in Social Science, 2025)
Dry ports are essential for efficient maritime port operations and can contribute to economic growth. Skikda, a city on the Mediterranean coast, is a significant hub for international trade and transportation, with its port playing a significant role in the country’s economy. However, the closure of Skikda’s dry port has had negative consequences on the city and the region, leading to job losses, reduced port efficiency, and hindered local business growth. Dry ports are essential for efficient logistics operations, improving connectivity, reducing transportation costs, and creating jobs. A comprehensive logistics strategy is essential to address the challenges faced by Algerian ports, particularly through the development of dry ports and supporting infrastructure. This strategy should evaluate the economic impact of dry port closures, the potential benefits of reopening facilities like Skikda’s dry port, and their role in multimodal transportation. Additionally, it should consider the effects of globalization and containerization on port operations, as well as the specific challenges Algerian ports face, such as aging infrastructure and bureaucratic inefficiencies. Reopening Skikda’s dry port could yield significant benefits, including job creation, improved logistics, and economic growth.